RESPONSE TO DEMAND UNCERTAINTY OF SUPPLY CHAINS: A VALUE-FOCUSED APPROACH WITH AHP AND TOPSIS - Chen, James; Lo, Sonia; Liu, Tong-Sheng (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
This paper aims to develop a management framework that can assist managers identify the risks in their supply chain, and assess potential solutions for these risks. Two multi-attributed decision analysis tools, namely, analytic hierarchy process (AHP) and technique for order of preference by similarity to ideal solution (TOPSIS) are utilized. The framework proposed is implemented in one electronics company in Taiwan, with three plants in mainland China. With this framework, the case company identifies four sorts of risks in their supply chain, e.g. production, labor, material, and fulfilment, and further determines which plant is most appropriate for order allocation. Further, this framework assists the company to reveal the weakest functions of each factory. As such it facilitates the company in making decisions of the resource allocation among the three plants. It thus contributes to supply chain managers in evaluating the risk factors of each manufacturing site and developing appropriate strategy.